Delivering Fiscal Squeeze by Cutting Local Government Spending1. (15th September 2015) - Innes, David; Tetlow, Gemma
Abstract: The financial crisis of 2008 and associated recession led to a permanent deterioration in the outlook for the UK's public finances. As part of the fiscal consolidation implemented by the UK government, grants to local authorities in England were cut by more than a third in real terms between 2009–10 and 2014–15. With limited revenue‐raising powers, these cuts meant drastic reductions in local authority spending in total and per person: local authority spending per person fell in real terms by 23.4 per cent over this period. But the size of spending cuts per person differed greatly across local authorities, ranging from 46.3 per cent to 6.2 per cent. On average, the distribution of the cuts across authorities does not seem to reflect the principle of 'equalisation' that was, at least in theory, in place up until 2013–14; the local authorities with least revenue‐raising capacity (which are typically the most deprived) have on average actually seen the largest spending cuts. Moreover, this pattern looks set to continue over the next five years, with those authorities that have seen the largest cuts to date also expected to see the largest cuts in future.